ENTANGLED HISTORIES IN PALESTINE/ISRAEL ([S.l.])
1 online resource
Keywords: This edited volume offers a new critical approach to the study of Zionist history and Israeli-Palestinian relations, based on the encounter between history and anthropology. Informed by the anthropological method of setting large questions to intimate settings, the book examines processes of Zionist colonization, nation-building and Palestinian dispossession by focusing on encounters between members of different national, religious and ethnic groups from below--through paying close attention to life stories and reconstructing everyday practices and micro-histories of places and communities. Thus, it tells a complex story in which the practices of historical actors are not simply reducible to a single underlying logic of colonization, even as they participate in the production and reproduction of colonial structures. This approach effectively undermines the prevailing tendency to study national communities in isolation, projecting onto the past an essentialist and rigid separation. Rather than assuming two clearly bounded and monolithic national groups, caught from the start in perpetual conflict, this volume probes their historical production through their evolving relationships, and their varied and shifting political, social, economic and cultural manifestations. The book will be of interest to students and researchers in an array of fields, including the history of Israeli-Palestinian relations, anthropological perspectives on settler colonialism, and Zionism.